THE ROLE OF WORK ENGAGEMENT MEDIATION IN THE RELATIONSHIP BETWEEN JOB INSECURITY, ROLE AMBIGUITY AND EMPLOYEE PERFORMANCE AT THE HEALTH SOCIAL SECURITY ADMINISTRATOR AGENCY (BPJS) LANGSA BRANCH OFFICE AND LHOKSEUMAWE BRANCH OFFICE - Fazila Monivatu Zahda; Nur Faliza; Teuku Zulkarnaen; Darmawati; Aiyub; Ibrahim Qamarius (RADJA PUBLIKA, 2024)
This study aims to examine the effect of job insecurity and role ambiguity on employee performance with work engagement as an intervening variable at the Social Security Administration Agency (BPJS) Health, Langsa and Lhokseumawe Branch Offices. The number of respondents in this study was 120 employees at the BPJS Health, Langsa and Lhokseumawe Branch Offices. The data analysis method used was Partial Least Square with Smart PLS Software. The results of this study found that job insecurity did not have a significant effect on work engagement and employee performance, while role ambiguity had a negative and significant effect on work engagement and employee performance and work engagement had a positive and significant effect on employee performance. The results of the mediation test found that work engagement was unable to mediate the relationship between job insecurity and employee performance, but work engagement was able to mediate the relationship between role ambiguity and employee performance partially (Partial Mediation)